A better way to perform orthognathic surgery in partially edentulous patients: A novel modified wafer design. Issue 1 (January 2022) - Dunphy, Benjamin; Adly Ghaly, Ghaly; Bowman, Peter; Sivamurthy, Gautham; McIntyre, Grant
Abstract : Introduction : Orthognathic surgery in the partially edentulous population presents multiple challenges. This case series aims to evaluate the success a novel modified wafer in orthognathic surgery for partially edentulous patients. Methods : Six partially edentulous patients eligible for orthognathic surgical treatment are included in this study; including one who had a fully edentulous maxilla. In two cases, the indication for surgery was to replace defective TMJ prostheses. 3-dimensional surgical planning was undertaken with computerised software. Three patients had bimaxillary osteotomies and one had a bilateral sagittal split osteotomy of the mandible. New prosthetic TMJs were placed in two cases in addition to orthognathic movements. Novel modified wafers and intermaxillary fixation screws were used intra-operatively in all cases. Results : All patients had good functional outcomes from surgery. Long-term occlusal stability was achieved with acrylic dentures. Mean age of the cohort was 55.8 years. The post-operative length of stay in hospital is comparable to the literature. Two patients had fixation plates removed after surgery. Conclusions : Using novel modified wafers, and intermaxillary fixation screws, in orthognathic surgery is safe and effective for partially edentulous patients. This technique has proven effective in both orthognathic and TMJ replacement surgery.